Immunohistochemical localization of calbindin-D28k in the cerebellum of rat - Timurkaan, S; Girgin, A (Indian Veterinary Journal, 2004)
Calbindin-D28k was first observed in the chicken duodenal mucosa as a protein, which is induced by vitamin D (Wassermann and Taylor, 1966). Calbindin-D28k is present in all vertebrate species and in a range of different cells (Heizmann and Braun 1995). The same protein was identified in the central nervous system (Taylor, 1974) and later shown to be a marker for neurons (Jande et al.,1981; Roth et al., 1981). Calbindin synthesis in intestine, kidney and pancreas is regulated by 1,25 dihidroxy-vitamin D3, however calbindin expression in neuronal tissue is independent of this hormone (Christakos et al., 1989). The localization of calbindin is within the cell body, dendrites and axons of specific populations of nerve cells, as well as in the nucleus (German et al., 1997). In the nervous system, calbindin is primarly associated with long axon neurons, exemplifed by thalamic projection neurons, cerebellar Purkinje cells, large spinal, retinal, cochlear and vestibular ganglion cells (Celio, 1990). Antibodies against calbindin-D28k are used as a neuro-anatomical markers (Celio loc. cit.). Calbindin is believed to act as a calcium buffer, which may modulate cytosolic Ca+2 transients and thus protect nerve cells (Heizman and Braun 1992, Wassermann and Fulmer 1983).
Keywords: Calcium-Binding Protein; Vitamin-D; Nervous-System; Neurons; Brain